Embodied Emotion Regulation: The Influence of Implicit Emotional Compatibility on Creative Thinking - Wu, Li; Huang, Rong; Wang, Zhe; Selvaraj, Jonathan Nimal; Wei, Liuqing; Yang, Weiping; Chen, Jianxin (Frontiers in Psychology, 2020)
The regulatory effect of embodied emotion on one’s general emotion and the impact of the compatibility or incompatibility of the two types of emotion on creative thinking are still debatable. The purpose of this study is to investigate these issues experimentally. In Experiment 1, participants completed an explicit positive and negative emotion test (PANAS) and an implicit positive and negative emotion test (IPANAT) twice on a computer after emotional video priming was used to induce negative emotions and facial expression manipulation was performed to induce embodied positive or negative emotions. It was found that maintaining the expression of a suppressed smile was helpful in regulating negative emotions (p = 0.047). Specifically, the implicit negative emotions induced by facial expression manipulation had a positive regulating effect on the implicit negative emotions induced by the video (T1: M = 47.813 to T2: M = 44.188). In Experiment 2, the positive or negative emotions of the participants were induced using emotional videos, and facial expression manipulation was used to induce their embodied positive or negative emotions. Then, the participants completed a creative test by completing alternative use tasks (AUTs) and Chinese character riddles. The AUT fluency score in the emotionally compatible group was significantly higher than that in the emotionally incompatible group (p = 0.032), but while experiencing negative emotions, the emotionally compatible group had a significantly higher originality score and insight in Chinese character riddle score than the emotionally incompatible group (p = 0.017, p = 0.004). Therefore, embodied negative emotion has a significant regulating effect on implicit negative emotion. The compatibility of emotion activated by facial expression and viewing a video contributes to creative thinking, while the incompatibility of emotion hinders creative thinking. The compatibility of emotion under positive emotions improved thinking fluency, while under negative emotions, it activated originality and insight in creative thinking. The influence of such emotional compatibility on creative thinking may be due to the regulating effect of embodied emotions on implicit emotions induced by emotional stimuli.